Nuevos apuntes epigráficos en manuscritos de temática eclesiástica de la Biblioteca Nacional de España - Balbín Chamorro, Paloma; Martino García, David; Moreno Benito, Arturo (Guillermo Escolar Editor, 2025)
En este artículo presentamos tres manuscritos de temática eclesiástica conservados en la Biblioteca Nacional de España (mss. BNE 1321, 8988 y 18387), fechados en los siglos xvii y xviii, que contienen anotaciones sobre inscripciones romanas y visigodas de Hispania. Nuestro objetivo es contribuir con ellos al vaciado exhaustivo de los manuscritos custodiados en esa institución y resaltar la utilidad que tiene para la epigrafía el análisis sistemático de obras aparentemente no relacionadas con la epigrafía o con la historia antigua.
New Epigraphical Contributions from Ecclesiastical Theme Manuscripts at the National Library of Spain
We present in this article three manuscripts of ecclesiastical theme preserved in the National Library of Spain (mss. BNE 1321, 8988, and 18387), dated on the 17th and 18th centuries, which contain annotations on Roman and Visigothic inscriptions from Hispania. Our aim is to contribute to the comprehensive study of the manuscripts held in that institution. Also, the paper aims to highlight the utility of the systematic analysis of seemingly unrelated works to Epigraphy or Ancient History.
Keywords: epigrafía; Hispania romana; inscripciones musivarias; falsos epigráficos; transmisión manuscrita; epigraphy; Roman Hispania; mosaic inscriptions; epigraphical fakes; manuscript tradition